Synopsis: The rapid expansion of herbicide use in smallholder agriculture in Ethiopia: Patterns, drivers, and implications - Tamru, Seneshaw; Minten, Bart; Alemu, Dawit; Bachewe, Fantu Nisrane (International Food Policy Research Institute, 2016)
We use qualitative and quantitative information from a number of datasets to study the adoption patterns and labor productivity impacts of herbicide use by farmers in Ethiopia. We find a four-fold increase in the value of herbicides imported into Ethiopia over the last decade, primarily by the private-sector. Adoption of herbicides by smallholders has grown rapidly over this period, with the application of herbicides on cereals doubling to more than a quarter of the area under cereals between 2004 and 2014. Relying on data from a large-scale survey of producers of teff, the most widely grown cereal in Ethiopia, we find significant positive labor productivity effects of herbicide use of between 9 and 18 percent. We show that the adoption of herbicides is strongly related to proximity to urban centers, levels of local rural wages, and access to markets. All these factors have changed significantly over the last decade in Ethiopia, explaining the rapid take-off in herbicide adoption. The significant increase in herbicide use in Ethiopia has important implications for rural labor markets, potential environmental and health considerations, and capacity development for the design and effective implementation of regulatory policies on herbicides.